1966
DOI: 10.2118/1227-pa
|View full text |Cite
|
Sign up to set email alerts
|

Application of Air-Mercury and Oil-Air Capillary Pressure Data In the Study of Pore Structure and Fluid Distribution

Abstract: Many physical properties of the porous media-immiscible liquid system are dependent upon the distribution of fluids within the pores; this in turn, is primarily a function of pore structure, liquid-liquid interfacial tension and liquid-solid wetting conditions. The capillary pressure hysteresis process provides a means of investigating the influence of pore structure upon fluid distribution for consistent surface conditions. Investigations indicate that residual non-wetting-phase saturations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 0 publications
1
50
1
Order By: Relevance
“…Pickell [31] highlighted that for water-wet rocks (i.e. like Fontainebleau), capillary forces predominate in the distribution of fluids and that viscous forces in the range normally of interest in the reservoir have a minimum influence on residual oil saturation [31].…”
Section: Di-electrical Measurementsmentioning
confidence: 99%
“…Pickell [31] highlighted that for water-wet rocks (i.e. like Fontainebleau), capillary forces predominate in the distribution of fluids and that viscous forces in the range normally of interest in the reservoir have a minimum influence on residual oil saturation [31].…”
Section: Di-electrical Measurementsmentioning
confidence: 99%
“…During laboratory core analyses, such as those described above, a very good correlation has been documented between capillary pressure (excess pressure of the non-wetting fluid), the initial saturation of the non-wetting fluid, and the residual saturation, as shown in Figure 2 (Pickell et al, 1966;Wardlaw and Taylor, 1976;and Chatzis and Dullien, 1981). These researchers observed that as porous media is exposed to progressively higher non-wetting phase pressures the maximum (initial) saturation of the non-wetting phase also increased, as is depicted by points (1), (2), and (3) in Figure 2.…”
Section: Laboratory Methods In Petroleum Applicationsmentioning
confidence: 87%
“…As described earlier, laboratory coreflood methods produce higher estimates for residual saturation than insitu tracer test determinations of residual saturation because the laboratory methods force large initial NAPL saturation throughout the entire pore space of the sample and displace water from progressively smaller pores (Morrow, 1987 andPickell et al, 1966). During laboratory core analyses, such as those described above, a very good correlation has been documented between capillary pressure (excess pressure of the non-wetting fluid), the initial saturation of the non-wetting fluid, and the residual saturation, as shown in Figure 2 (Pickell et al, 1966;Wardlaw and Taylor, 1976;and Chatzis and Dullien, 1981).…”
Section: Laboratory Methods In Petroleum Applicationsmentioning
confidence: 99%
See 2 more Smart Citations